Improving the methane productivity of anaerobic digestion using aqueous extracts from municipal solid waste incinerator ash. (15th April 2020) - Shamurad, Burhan; Gray, Neil; Petropoulos, Evangelos; Tabraiz, Shamas; Sallis, Paul
Abstract: This study investigated the effects of mineral waste extracts (MWE) on laboratory-scale two-stage anaerobic digesters treating synthetic organic waste. MWE was prepared as aqueous extracts from different ash samples (incineration bottom ash (IBA), fly ash (FA) and boiler ash (BA) taken from a municipal solid waste incineration plant. At 20 days hydraulic retention time, all three MWE stimulated hydrogen production in their respective acidogenic reactor by around 35% (c.f. control acidogenic reactor), whilst no difference was seen in the methane productivity of the linked methanogenic reactors (average 527 ± 45 mL CH4 /g VS, including control methanogenic reactor). Following a step reduction in hydraulic retention time from 20 to 10 days and a doubling of the organic loading rate from 2.5 g to 5 g VS/L. d, no significant change was seen in hydrogen production (p > 0.05) in the acidogenic reactor amended with MWE from IBA and BA, or the control acidogenic reactor. However, the acidogenic reactor receiving MWE from FA had 45% lower hydrogen productivity. The step change in hydraulic retention time and organic loading rates led to the failure of most methanogenic reactors (≤100 mL CH4 /g VS), however, the one receiving feed containing MWE from IBA showed stable performance without signs of failure, and had higher volumetric methane productivity, albeit at lower methane yields (370 ± 20 mL CH4 /g VS). 16S rRNA analysis using the Illumina sequencing platform revealed acidogenesis by Lactobacillaceae in the acidogenic reactor and syntrophic acetate oxidation by Synergistaceae linked to enrichment of the candidatus genus Methanofastidiosum, in the stable methanogenic reactor receiving MWE from IBA. Graphical abstract: Image 1 Highlights: Effects of mineral waste extracts on anaerobic digestion were studied. Mineral waste extracts increased hydrogen production in acidogenic reactors. Mineral waste extracts enhanced performance of methanogenic reactors. Mineral waste extracts affected microbial community composition and function.